Policosanol ameliorates testicular injury and improves steroidogenesis in diabetic hypercholesterolemic rats - Rana G. Eissa; Mohamed M. Elseweidy; Sara E. Elhamly; Abd Elmonem A. Ali; Sally K. Hammad (Molecular Biology Reports, 2026)

Beyond toxicity: Systems-level virulence of entomopathogenic fungi in termite social immunity - Hafiz Muhammad Usman; Hammad Hassan; Arshad Ali; Mohammad Mazharul Karim; Ali Hassan; Min Lu (Journal of Invertebrate Pathology, 2026)

Engineering MOF-on-MOF heterostructure for enhanced adsorption-assisted photocatalytic decontamination of carbamazepine: Kinetics, thermodynamic and pathway study - Muhammad Fayaz; Raza Ullah; Muzamil Ahmad; Ikram Ullah; Muhammad Rafiq; Ali Ahmad; Nasim Ullah; Faizan Jamil; Latif Ur Rehman; Hammad Ali; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2026)

Effect of predatory pressure on behavior of termite Reticulitermes chinensis - Hammad Hassan; Ali Hassan; Taqi Raza; Hafiz Muhammad Usman; Arshad Ali; Jinli Ding; Qiuying Huang; Min Lu (Journal of Insect Physiology, 2026)

Seroprevalence and risk factors of Mycobacterium avium subsp. paratuberculosis in dromedary camels of Southern Punjab, Pakistan - Aliza Ali; Mughees Aizaz Alvi; Muhammad Hammad Hussain; Muhammad Numan; Junaid Ahmad; Muzafar Ghafoor; Muhammad Khalid Mansoor; Muhammad Saqib (Tropical Animal Health and Production, 2026)

Bridging iron biofortification through integrative strategies from QTL mapping to regulatory-compliant genome editing - Sadia Hakeem; Safia Khushi; Muhammad Hammad Nadeem Tahir; Nadia Hussain Ahmed; Amna Bibi; Zulfiqar Ali (Cereal Research Communications, 2026)
Around two billion people are affected by iron (Fe) malnutrition globally, largely contributed by the consumption of cereal-based diets with low levels of iron and reduced bioavailability due to presence of inhibitor compounds like phenols and phytic acid. Among several methods of enhancing Fe content of staples, genetic biofortification is the most sustainable, and cost-effective method. Genetic biofortification through conventional breeding has succeeded in producing a number of cultivars marketed for high nutrition. However, this approach is limited due to the requirement of large genetic variation, long breeding time, phyto-availability of nutrients through soil only, gene targeting in compatible species only, lack of knowledge of QTL and genetic maps, environmental interactions, risk of linkage drag, and complex interrelations among nutrients as well as with other yield traits. With the advent of genomic approaches for targeted genetic manipulation, transgenic approach offers straightforward and robust techniques to genetically biofortify staples. While transgenic approaches to increasing Fe content have been helpful, genetically modified (GM) cultivars for staple crops may be delayed due to GM regulatory barriers. This chapter reviews the global status of Fe malnutrition, possible solutions to combat its deficiency, and bottlenecks towards Fe biofortification in staples. It also provides insights into transgenic approaches to address this issue as well as way forward to resolve the regulatory issues associated with GM crops by providing alternate options.

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

HLH disease mimic triggered by anaplasmosis in a patient with SLE scleroderma Sjogren overlap syndrome: A case report - Areeba Minhaj; Marium Minhaj; Hammad Chaudhry; Emad Abusitta; Asad Ali Siddiqui; Ali Nazim (Next Research, 2026)

Bioremediation of Heavy Metal Contamination through CaSO₄ Application Under Sewage Water Irrigation Enhances Plant Physiology and Antioxidant Defense in Tomato - Rashid Jawad; Shaghef Ejaz; Aamir Nawaz; Hafiz Mohkum Hammad; Sajid Ali; Farhat Abbas; Artemi Cerdà (Journal of Soil Science and Plant Nutrition, 2026)

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

Insecticidal and antibacterial potential of Croton tiglium functionalized zinc oxide nanoparticles - Arshad Ali; Ali Hassan; Imran Afzal; Hammad Hassan; Kirshan Chand; Hafiz Muhammad Usman; Xiaolong Liu; Min Lu (International Journal of Tropical Insect Science, 2026)

Evaluating the performance of high-resolution climate simulations over the central himalaya and Karakoram - Tika Gurung; Liang Chen; Syed Hammad Ali; Clinton Rowe; Francisco Munoz Arriola; Randall S. Ritzema (Climate Dynamics, 2026)

Competitive adsorption of antibiotics on waste-derived hybrid biochar: Performance, mechanism, and life cycle assessment - Ali Hamid; Ahsan Jalal; Muhammad Arshad; Muhammad Usama; Sajjad Hussain; Hammad Khan (Journal of Environmental Chemical Engineering, 2026)

Synergistic NiO-Pt heterostructure for enhanced hydrogen evolution: Boosting charge transfer and catalytic efficiency in alkaline media - Faria Rafique; Shahzad Ameen; Muhammad Hammad Ali; Aleena Tahir; Hamayal Shahzad; Amina Bhatti; Tanveer ul Haq; Mira Tul Zubaida Butt; Ammar Ahmed Khan; Saleh A. Ahmed; Irshad Hussain; Habib Ur Rehman (Fuel, 2026)

From half-cells to full-cells: across-scale comparative evaluation of lanthanum-based perovskites as high-performance anode materials for the oxygen evolution reaction - Blaž Toplak; Leon Müller; Ali Raza Khan; André Olean-Oliveira; Khuzaifa Yahuza Muhammad; Wang Feng; Raíssa Ribeiro Lima Machado; Da Xing; Mohammed-Ali Sheikh; Leander Kucklick; Ahammed Suhail Odungat; Adarsh Jain; et al. (Chemical Engineering Journal, 2026)

Quinazolinone based broad-spectrum antiviral molecules: design, synthesis, in silico studies and biological evaluation - Abdallah E. Abdallah; Omkulthom Al kamaly; Esmail M. El-Fakharany; Yousra A. El-Maradny; Abdelaaty A. Shahat; Mohamed S. Alesawy; Ali Hammad; Mohamed Ayman El-Zahabi; Samiha A. El-Sebaey; Mona S. El-Zoghbi (Molecular Diversity, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Targeting Reactive Astrocytes with Flavonoids to Alleviate Neuroinflammation and Promote Synaptic Function - Devendra Pratap Rao; Ammar Kh. Hammad; Hussein Riyadh Abdul Kareem Al-Hetty; Ali K. Kareem; Ahmed Hjazi; Irfan Ahmad; Zahraa Abbas; Reham Yahya Albaz; Yasser Fakri Mustafa; Mashael Abdulmohsin Zuhair Abdulmoaty (Molecular Neurobiology, 2026)

Insecticidal and antibacterial properties of zinc oxide nanoparticles (ZnO-NPs) synthesized from Phoebe zhennan leaf extract - Arshad Ali; Kirshan Chand; Chenghu Liu; Asfandyar; Ali Hassan; Hammad Hassan; Xiaolong Liu; Min Lu (Journal of Asia-Pacific Entomology, 2025)

Sustainable biodiesel production via Alkanna tinctoria oil Conversion: A multi-method modeling approach utilizing crab shell-derived biochar catalysts - Ali Hamid; Hammad Khan; Arsalan Arif; Muhammad Arshad; Sajjad Hussain; Arslan Maqbool (Biomass and Bioenergy, 2025)

Dermatomyositis: focus on cutaneous features, etiopathogenetic mechanisms and their implications for treatment - Hammad Ali; Aretha On; Enze Xing; Catherine Shen; Victoria P. Werth (Seminars in Immunopathology, 2025)
Dermatomyositis (DM) is an infrequently encountered idiopathic inflammatory myopathy distinguished by distinctive cutaneous manifestations and/or progressive muscle weakness. This review provides an updated exploration of DM, emphasizing cutaneous features, etiopathogenesis, and therapeutic implications. DM presents a heterogeneous spectrum, ranging from classic forms involving both skin and muscle to clinically amyopathic DM, which lacks significant muscle involvement but carries risks like interstitial lung disease (ILD) and malignancy. Recent advances in understanding DM pathogenesis underscore the roles of myositis-specific autoantibodies, type I interferons, and cytokine dysregulation in disease activity and clinical outcomes. Specific antibodies such as anti-Mi-2, anti-TIF1γ, and anti-MDA5 define subtypes of DM, aiding diagnosis, prognosis, and tailored management strategies. While conventional immunosuppressive therapies like glucocorticoids and antimalarials form the cornerstone of treatment, many cases remain refractory, particularly involving chronic skin disease. Emerging targeted therapies, including Janus kinase inhibitors and monoclonal antibodies, show promise in addressing type I interferon-driven pathways and refractory symptoms. Future research aims to refine diagnostic criteria, integrate biomarkers, utilize more robust outcome measures, and develop targeted therapeutics to improve outcomes while minimizing treatment-related toxicity. This review consolidates current knowledge and highlights the need for a multidisciplinary, individualized approach to managing DM, focusing on both established and novel treatment avenues.

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Dolomitized stromatolites during regressive-transgressive cycles in the Cambrian Abbottabad Formation, Pakistan: depositional environment, sequence stratigraphic significance, and paleogeographic implications - Syed Kamran Ali; George Kontakiotis; Tariq Mahmood; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Ahmer Bilal; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2025)

Effect of entomopathogenic fungus Beauveria bassiana on behavior of termite Reticulitermes chinensis - Hammad Hassan; Ali Hassan; Taqi Raza; Jinli Ding; Arshad Ali; Qiuying Huang; Min Lu (Journal of Invertebrate Pathology, 2025)

Comprehensive study on efficient diclofenac sodium removal using walnut and pistachio shell activated carbon: ANN, kinetics, isotherms, thermodynamics and DFT calculations - Sinem Temiz Seymen; Handan Atalay Eroğlu; Elif Nihan Kadıoğlu; Muhammad Umar; Ali Hamid; Hammad Khan; Sajjad Hussain; Feryal Akbal (Biomass and Bioenergy, 2025)

Sustainable wastewater treatment via nitrogen/sulfur co-doped graphene composite: Mechanistic insights & process optimization - Humaira Seema; Muhammad Arshad; Arslan Maqbool; Sumbal Zeb; Ali Hamid; Muhammad Umar; Sajjad Hussain; Hammad Khan (Journal of Water Process Engineering, 2025)

Modeling of Soil Organic Carbon Distribution in Mangrove Forests along the Southern Egyptian Red Sea Coast - Ebrahem M. Eid; Fadl A. Hashem; Alaa A. Khalil; Beelal A. A. Ali; Abdelwahab A. Afefe; Eman A. A. Ahmad; Walaa N. A. Ibrahim; Rania B. S. Badr; Hossam H. Hammad (Journal of Soil Science and Plant Nutrition, 2025)

Adsorption of 4-bromophenol from simulated wastewater using magnetic carbon-based composites: Kinetics, equilibrium, thermodynamics, and density functional theory analysis - Beatris L. Mello; Pascal S. Thue; Ali Hamid; Muhammad Usama; Fernando Machado Machado; Moaaz K. Seliem; Younes Dehmani; Glaydson S. dos Reis; Mohamed Abdel Salam; Hammad Khan; Luis F.O. Silva; Eder C. Lima (Journal of Water Process Engineering, 2025)

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

Importance of an Oncology Interest Group in Medical School: Experience from a Developing Country - Hammad Atif Irshad; Abdul Rehman; Muhammad Ali Akbar Khan; Dahir Ashfaq; Munira Moosajee (Journal of Cancer Education, 2025)

Probiotics Attenuate Myopathic Changes in Aging Rats via Activation of the Myogenic Stellate Cells - Nehal H. M. Abdel-Halim; Eman A. E. Farrag; Maha O. Hammad; Ola Ali Habotta; Hend M. Hassan (Probiotics and Antimicrobial Proteins, 2025)
Aging represents a complex biological process associated with decline in skeletal muscle functions. Aging impairs satellite cells that serve as muscle progenitor cells. Probiotic supplementation may have many beneficial effects via various mechanisms. We examined the possible effects of probiotics in stimulating the proliferation of myogenic stellate cells in aging rats . Twenty-four male albino Sprague–Dawley rats were classified equally into four groups: adult control, old control, adult + probiotics, and old + probiotics. Probiotics (Lactobacillus LB) were administered gavage at a dose of 1 ml (1 × 10 9 CFU/ml/day) for 4 weeks. A significant increase in the relative gastrocnemius weight ratio and improvement of contractile parameters was detected in the old + probiotics group (0.6 ± 0.01) compared to the old control group (0.47 ± 0.01; P < 0.001). Probiotics significantly upregulated the activities of GSH, while NO and MDA were markedly decreased compared to control groups ( P ≤ 0.001). Also, probiotics increased the mRNA and protein expressions of myogenin and CD34 ( P < 0.05) as determined by real-time PCR and immunohistochemistry. Moreover, the old + probiotics group showed apparent restoration of the connective tissue spaces, reflecting the all-beneficial effects of probiotics. Our findings indicated that probiotics attenuated myopathic changes in aging rats probably through activation of the myogenic stellate cells. Probiotics improved the muscle weight, function, antioxidant activity, and myogenic transcription factors of the skeletal muscle.

Rhoifolin as a potential anxiolytic drug for the effects of nicotine withdrawal: beneficial effects on behavior, neuroinflammation, and oxidative stress - Alaa M. Hammad; Suhair Sunoqrot; Thanaa Al-zuhd; Mohammed Waleed; Ali I. M. Ibrahim; F. Scott Hall; Alaa R. Al-Tamimi; Eveen Al-Shalabi (Metabolic Brain Disease, 2025)

Crotalaria burhia Buch. -Ham.: a comprehensive review of its botany, traditional uses, phytochemistry, and pharmacology - Sirajudheen Anwar; Hammad Saleem; Tania Azmat; Umair Khurshid; Kashif Maqbool Khan; Tahir Ali Chohan; Anjum Khursheed; Abdulwahab Alamri; Nasser A. Awadh Ali (Natural Product Research, 2025)

Retraction Note: Enhancement of cardiac angiogenesis in a myocardial infarction rat model using selenium alone and in combination with PTXF: the role of Akt/HIF-1α signaling pathway - Mohamed M. Elseweidy; Sousou I. Ali; Mohamed A. Shaheen; Asmaa M. Abdelghafour; Sally K. Hammad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Performance and data acquisition from low-cost air quality sensors: a comprehensive review - Mubashir Ali Siddiqui; Mirza Hammad Baig; Muhammad Uzair Yousuf (Air Quality, Atmosphere & Health, 2025)

Effect of resveratrol on post-thaw motility, kinematics, structural parameters and antioxidant/oxidant status of Kamori buck spermatozoa - Tarique Hussain; Muhammad Hammad Fayyaz; Amjad Hameed; Syed Murtaz Hassan Andrabi; Rehana Kausar; Yasin Mubashir; Iqra Batool; Muhammad Shahzad; Ali Dogan Omur (Cryobiology, 2025)

Effects of dietary organic selenium, vitamin C, and vitamin E supplementation on growth performance, serum biochemistry, and antioxidant status in juvenile Hypophthalmichthys molitrix - Hairui Yu; Maida Mushtaq; Saira Razzaq; Umar Ali; Muhammad Khan; Abdur Rahman; Guobo Quan; Mehroze Fatima; Saima Naveed; Muhammad Hammad Zafar; Muhammad Aziz ur Rahman (Frontiers in Marine Science, 2025)
The study aimed to evaluate the effects of dietary supplementation of selenium (Se), vitamin C, and vitamin E on growth performance, meat quality, and antioxidant status in Hypophthalmichthys molitrix juveniles. A total of 480 juveniles (mean weight: 20 ± 0.29 g) were randomly assigned to 24 aquaria (20 fish per 100 L), which were allocated to eight dietary treatments (three aquaria per treatment) following a completely randomized design. The dietary treatments included: (1) a basal diet without supplementation (Control), (2) selenium supplementation (S), (3) vitamin C supplementation (C), (4) vitamin E supplementation (E), (5) selenium and vitamin C supplementation (SC), (6) selenium and vitamin E supplementation (SE), (7) vitamin C and vitamin E supplementation (EC), and (8) selenium, vitamin C, and vitamin E supplementation (SCE). The supplementation levels were 0.9 mg/kg Se, 300 mg/kg vitamin C, and 100 mg/kg vitamin E, respectively. After a one-week acclimatization period, a 10-week growth trial was conducted. Fish fed the SCE diet exhibited significantly higher (p< 0.05) final weight gain, body length gain, body weight gain percentage, and specific growth rates compared to other treatments. Selenium concentrations in the kidney, liver, pancreas, and muscle were significantly higher (p< 0.05) in the SCE, SC, SE, and EC groups compared to the Control and single-supplement groups. Hematological parameters, including WBC, RBC, HGB, HCT, and MCHC, were significantly higher (p< 0.05) in the SCE group compared to all other groups. Similarly, serum activities of ALT, AST, and ALP were significantly lower (p< 0.05) in the SCE group than in other treatments, while blood glucose levels were unaffected (p > 0.05) by dietary treatments. Antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were significantly enhanced (p< 0.05) in the whole body and muscle tissues of fish receiving Se, vitamin C, and E supplementation. Thiobarbituric acid reactive substances (TBARS) levels in muscle and serum were significantly higher (p< 0.05) in the Control group compared to all supplemented groups. The proximate composition of meat, including dry matter, fat, ash, and protein contents, was not significantly affected (p > 0.05) by the dietary treatments. In conclusion, dietary supplementation of selenium, vitamin C, and vitamin E significantly improved growth performance, selenium deposition in tissues, and antioxidant status of Hypophthalmichthys molitrix juveniles, without adversely affecting meat chemical composition.

From pollutant to purifier: Leveraging plastic waste-derived activated carbon for sustainable water remediation solutions - Hammad Khan; Muhammad Usama; Mohammad Ilyas Khan; Fazal Wahab; Izhar Ahmad; Ali Hamid; Sajjad Hussain; Arslan Maqbool (Journal of Environmental Management, 2025)

Differential effects of liraglutide naltrexone/bupropion, and caloric restriction on metabolic parameters and beta-cell regeneration in type 2 diabetic rat model: role of beta arrestin 1 - Dina H. Merzeban; Amani M. El Amin Ali; Reem O. Hammad; Mohamed H. Elmahdi; Marwa A. Sofi; Rania H. Mahmoud; Sayed M. Metwally; Ahmed M. El Ebiary (Journal of Molecular Histology, 2025)

Aliphatic substrates-mediated unique rapid room temperature synthesis of carbon quantum dots for fenofibrate versatile analysis - Ali Abdel-Hakim; Fathalla Belal; Mohamed A. Hammad; Abdelaziz Elgaml; Mahmoud El-Maghrabey (Analytica Chimica Acta, 2025)

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

Unveiling the biosorption performance of silk fibroin fiber for Pb(II) and Cr(VI) removal: Machine learning and DFT analysis - Muhammad Usman Farooq; Hammad Khan; Muhammad Arshad; Muhammad Usama; Mohammad Ilyas Khan; Sajjad Hussain; Ali Hamid (Journal of Water Process Engineering, 2024)

Utilizing Cinnamomum verum (a culinary spice), as a functional food ingredient ameliorating hypercholesterolemia: In-vivo, in-vitro, and in-silico multi-model analysis - Mahnoor Bano; Muhammad Khurram Waqas; Talha Ali Chohan; Fakhra Batool; Aamir Mushtaq; Yahya I. Asiri; Mohd. Zaheen Hassan; Md Ali Mujtaba; Md. Khalid Anwer; Muhammad Irfan Sidique; Ayesha Riaz; Umair Khurshid; et al. (Food Bioscience, 2024)

Exome sequencing revealed variants in SGCA and SIL1 genes underlying limb girdle muscular dystrophy and Marinesco–Sjögren syndrome patients - Ali Faheem; Rizwan Masud; Rabea Nasir; Zeeshan Khalid Awan; Hammad Ali Nasir; Zara Khalid Khan; Hajra Fayyaz; Syed Irfan Raza (Molecular Biology Reports, 2024)

The interplay of PTEN and AKT nexus in breast cancer: a molecular perspective - Anum Kamal; Ali Raza Awan; Masood Rabbani; Hammad Raza Sheikh; Muhammad Tayyab; Sehrish Firyal; Imran H. Khan; Muhammad Wasim (Molecular Biology Reports, 2024)

Seasonal occurrence and ecological risk assessment of polycyclic aromatic hydrocarbons in the sediments and water in the left-bank canals of Indus River, Pakistan - Mohammed Hammad Siddiqui; Uzma Bhanbhro; Kaleemullah Shaikh; Shoaib Ahmed; Razia Begum; Sohail Shoukat; Waheed Ali Khokhar (Environmental Monitoring and Assessment, 2024)

Phloroglucinol ameliorated methylglyoxal induced harmful effects in rats - Hammad Ahmed; Talha Bin Fayyaz; Najeeb Khatian; Shumaila Usman; Yamna Khurshid; Bushra Sikandar; Uzair Nisar; Syed Abid Ali; Ghulam Abbas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Laboratory Investigation of Deep Soil Mixing for the Improvement of Salt-Cemented Soils - Mohammed A. Hammad; Yahia E.-A. Mohamedzein; Mohammed Y. Al-Aghbari; Ali S. Al-Nuaimi (Geotechnical and Geological Engineering, 2024)

Nutritional and medicinal plants as potential sources of enzyme inhibitors toward the bioactive functional foods: an updated review - Hammad Saleem; Anam Yaqub; Rabiya Rafique; Tahir Ali Chohan; Durr-e-Shahwar Malik; Muhammad Imran Tousif; Umair Khurshid; Nafees Ahemad; Ramasamy Ramasubburayan; Kannan RR Rengasamy (Critical Reviews in Food Science and Nutrition, 2024)

Genotype classification and pathogenicity of infectious bursal disease virus circulating in vaccinated broiler chicken farms - Samah M. Mosad; Mona M. Elsayed; Enas M. Hammad; Basma M. Hendam; Hanaa S. Ali; Abdelfattah H. Eladl; Mohamed A. Saif (Veterinary Research Communications, 2024)
This study investigated the genotype classification and pathogenicity of infectious bursal disease virus (IBDV) circulating in vaccinated broiler chicken farms in Egypt. A total of 150 samples were collected from 30 vaccinated commercial broiler chicken farms and pooled into 30 working samples. IBDV was tested using reverse transcriptase polymerase chain reaction (RT-PCR) amplification of the hypervariable region of the viral protein 2 (hvVP2) and the VP1 gene 5’ extremity. Both RT-PCR fragments were sequenced from six samples, and then the obtained nucleotide sequences were analyzed. The IBDV genotypes were identified using nucleotide sequences. Five sequences of the six strains examined were classified as genotype A3B2 for the highly virulent segments A and B (vv-A/vv-B IBDV). Interestingly, this study identified and classified a novel segment-reassortant strain as the A1B2 genotype. Specifically, it involved the segment reassortment of classical virulent segment A (cv-A) with vv-B producing cv-A/vv-B reassortant IBDV. Subsequently, we compared the pathogenicity of reassortant (cv-A/vv-B) IBDV and vvIBDV strains identified in this study. Both strains developed typical IBD clinical signs, postmortem lesions, histopathology, immunohistochemistry, and lesion scores, which were more severe in vvIBDV than reassortant IBDV. In conclusion, this is the first report of the genotype classification based on both genome segments (hvVP2 and VP1) with pathogenicity of IBDV circulating in vaccinated broiler chicken farms and this pathogenicity is more severe in vvIBDV strain than a novel reassortant IBDV strain.

The Cambrian sedimentology and reservoir properties of the hybrid Abbottabad Formation in the Kotli area, Sub-Himalaya, Pakistan: insights into the Proto-Tethys paleoenvironment - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Tariq Mahmood (Carbonates and Evaporites, 2024)

Assessing agricultural potential of abandoned land in the Euphrates basin: soil fertility modeling and geostatistical analysis - Jamal Abed Hammad; Soumaia M’nassri; Balkis Chaabane; Ali Hussein Ibraheem Al-Bayati; Rajouene Majdoub (Modeling Earth Systems and Environment, 2024)

RETRACTED ARTICLE: Enhancement of cardiac angiogenesis in a myocardial infarction rat model using selenium alone and in combination with PTXF: the role of Akt/HIF-1α signaling pathway - Mohamed M. Elseweidy; Sousou I. Ali; Mohamed A. Shaheen; Asmaa M. Abdelghafour; Sally K. Hammad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Ischemic heart diseases such as myocardial infarction (MI) are a global health problem and a leading cause of mortality worldwide. Angiogenesis is an important approach for myocardial healing following ischemia. Thus, this study aimed to explore the potential cardiac angiogenic effects of selenium (Se), alone and in combination with the tumor necrosis factor-alpha inhibitor, pentoxifylline (PTXF), via Akt/HIF-1α signaling. MI was induced in rats using two subcutaneous doses of isoprenaline (ISP) at a 24-h interval (150 mg/kg). One week later, rats were orally given Se (150 µg/kg/day), PTXF (50 mg/kg/day), or Se/PTXF combination. ISP-induced myocardial damage was evident by increased HW/TL ratios, ST segment elevation, and increased serum levels of CK-MB, LDH, and troponin-I. ISP increased the cardiac levels of the lipid peroxidation marker MDA; the pro-inflammatory cytokines IL-6, IL-1β, and TNF-α; and the pro-apoptotic protein Bax and caspase-3. In contrast, the cardiac levels of the antioxidant markers GSH and SOD and the anti-apoptotic marker Bcl-2 were reduced. Furthermore, ISP markedly increased the cardiac levels of p-Akt and HIF-1α proteins and the cardiac gene expression of ANGPT-1, VEGF , and FGF-2 . Treatment with Se both alone and in combination with PTXF ameliorated the ISP-induced myocardial damage and further increased cardiac angiogenesis via Akt/HIF-1α signaling. Se/PTXF combined therapy was more beneficial than individual treatments. Our study revealed for the first time the cardiac angiogenic effects of Se both alone and in combination with PTXF in myocardial infarction, suggesting that both may be promising candidates for clinical studies. Graphical Abstract

The Role of RIN3 Gene in Alzheimer’s Disease Pathogenesis: a Comprehensive Review - Mostafa Meshref; Hazem S. Ghaith; Mohamed Ahmed Hammad; Mahmoud Mohamed Mohamed Shalaby; Faris Ayasra; Fatma Ahmed Monib; Mohamed S. Attia; Mahmoud A. Ebada; Hanaa Elsayed; Ali Shalash; Eshak I. Bahbah (Molecular Neurobiology, 2024)
Alzheimer’s disease (AD) is a globally prevalent form of dementia that impacts diverse populations and is characterized by progressive neurodegeneration and impairments in executive memory. Although the exact mechanisms underlying AD pathogenesis remain unclear, it is commonly accepted that the aggregation of misfolded proteins, such as amyloid plaques and neurofibrillary tau tangles, plays a critical role. Additionally, AD is a multifactorial condition influenced by various genetic factors and can manifest as either early-onset AD (EOAD) or late-onset AD (LOAD), each associated with specific gene variants. One gene of particular interest in both EOAD and LOAD is RIN3, a guanine nucleotide exchange factor. This gene plays a multifaceted role in AD pathogenesis. Firstly, upregulation of RIN3 can result in endosomal enlargement and dysfunction, thereby facilitating the accumulation of beta-amyloid (Aβ) peptides in the brain. Secondly, RIN3 has been shown to impact the PICLAM pathway, affecting transcytosis across the blood-brain barrier. Lastly, RIN3 has implications for immune-mediated responses, notably through its influence on the PTK2B gene. This review aims to provide a concise overview of AD and delve into the role of the RIN3 gene in its pathogenesis.

Study of the engineering performance of pipes buried in the soil - Mahmoud Ali Attia; Amr Mohamed Radwan; Amal Hammad; Ahmed Farag (Innovative Infrastructure Solutions, 2024)
This paper investigates the response of a flexible buried pipe to traffic load using laboratory experiments and numerical analysis. A series of laboratory tests and numerical simulations were performed to examine the effect of surface pressure, loading width, pipe type, pipe thickness, and burial depth on model response. In the experiments, a load was applied to the surface of a tank in which a pipe was buried. To gain a better understanding of the pipe's behavior, numerical simulations were performed using the finite element method; PLAXIS 2-D software. The results show that there is a good agreement between numerical and experimental test results. Furthermore, experimental and numerical analysis show that increasing burial depth reduces pipe deflection, increases soil surface settlement, and decreases pipe pressure, whereas increasing surface pressure increases all of the above parameters. Finally, equations were developed based on all numerical and experimental results to predict maximum stress on the pipe crown.

Assessing Asiatic black bear (Ursus thibetanus) temporal overlap and co-occurrence with sympatric species in the temperate zone of the Hindu Raj Mountain range - Faizan Ahmad; Muhammad Rehan; Eve Bohnett; Ammar Hassan; Sami Ullah; Shah Zeb; Hammad Ali Mian; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Reliable sustainable management strategies for flare gas recovery: technical, environmental, modeling, and economic assessment: a comprehensive review - Ahmed M. Elgarahy; Ahmed Hammad; Moustafa Shehata; Amir Ayyad; Mohamed El-Qelish; Khalid Z. Elwakeel; Ali Maged (Environmental Science and Pollution Research, 2024)

Derivatization-free CTAB-induced fluorescence sensing strategy for determination of daptomycin in environmental, pharmaceutical, and biological samples - Ali Abdel-Hakim; Fathalla Belal; Mohamed A. Hammad; Manar A. Nader; Mahmoud El-Maghrabey (Sustainable Chemistry and Pharmacy, 2024)

A systematic review on understanding the mechanistic pathways and clinical aspects of natural CDK inhibitors on cancer progression.: Unlocking cellular and biochemical mechanisms - Andleeb Asghar; Tahir Ali Chohan; Umair Khurshid; Hammad Saleem; Mian Waqar Mustafa; Anjum Khursheed; Ahmed Alafnan; Rahila Batul; Mohammed Khaled Bin Break; Khaled Almansour; Sirajudheen Anwar (Chemico-Biological Interactions, 2024)

Synergistic effects of hybrid microfibers on mechanical, thermal, and microstructural characterization of nanocomposites - Nabil Ben Kahla; Ali Raza; Ahmed Babeker Elhag; Hammad Haider (Environmental Science and Pollution Research, 2024)

Socio-environmental factors and solar housing system adoption: moderating effect of attitude - Ahsen Maqsoom; Muhammad Hammad; Muhammad Umer; Wesam Salah Alaloul; Hassan Ashraf; Muhammad Ali Musarat; Tahira Nazir (Innovative Infrastructure Solutions, 2024)

Synthesis and characterizations of conocarpus- and azadirachta-derived activated carbons as wastewater recycling material - Murtuza Mehdi; Mirza Hammad Baig; Masood Ahmad; Kamran Ali; Muhammad Mohib; Ali Farooqi; Mohammad Affan; Muhammad Mazin (Environmental Monitoring and Assessment, 2024)

Effect of riboflavin on redox balance, osmolyte accumulation, methylglyoxal generation and nutrient acquisition in indian squash (Praecitrullus fistulosus L.) under chromium toxicity - Habiba Kanwal; Syed Hammad Raza; Shafaqat Ali; Muhammad Iqbal; Mudassir Iqbal Shad (Environmental Science and Pollution Research, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

Application of coliphage as biocontrol agent in combination with gamma irradiation to eliminate multi-drug-resistant E. coli in minimally processed vegetables - Salwa A. Abou El-Nour; Ali A. hammad; Reham Fathy; Amal S. Eid (Environmental Science and Pollution Research, 2023)
Biofilm formation is a rising concern in the food industry . Escherichia coli ( E. coli ) is one of the most important food-borne pathogens that can survive in food and food-related environments and eventually produce biofilms. This study suggested that both coliphages used were successful in preventing the creation of new biofilms as well as removing existing ones. Confocal laser scanning microscopy verified these findings. According to the findings, neither coliphage survived at 37 °C, but both remained stable at 4 °C and − 20 °C for extended periods of time. The study revealed that both coliphages demonstrated a greater degree of gamma irradiation resistance when compared to E. coli . The study’s results indicate that the implementation of a dual method, which incorporates gamma irradiation (1.5 kGy) and coliphage treatment, on various kinds of vegetables that were infected with E. coli , resulted in a significant reduction in bacterial count (surpassing 99.99%) following a 24-h incubation period. Combining gamma irradiation and the coliphage approach was significantly effective at lowering polysaccharide concentrations and proteins in the biofilm matrix. The results revealed that the pairing of gamma irradiation and coliphages acted in conjunction to cause disruptions in the matrix of biofilm, thereby promoting cell removal compared with either of the individual treatments. Ca + ions strengthen the weak virion interaction with the relevant bacterial host cell receptors during the adsorption process. In conclusion, use of coliphage in combination with gamma irradiation treatment can be applied to improve fresh produce’s microbial safety and enhance its storability in supermarkets. Graphical Abstract

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Exploring the role of HaTIPs genes in enhancing drought tolerance in sunflower - Tania Safdar; Muhammad Hammad Nadeem Tahir; Zulfiqar Ali; Muhammad Habib ur Rahman (Molecular Biology Reports, 2023)

Effects of dietary nano-selenium supplementation on Riemerella anatipestifer vaccinated and challenged Pekin ducklings (Anas platyrhynchos) - Abdelfattah H. Eladl; Nehal M. Nabil; Amal Awad; Shereen Badr; Amera F. Ebrahem; Maram M. Tawakol; Enas Hammad; Hanaa S. Ali; Reham A. El-Shafei (Veterinary Microbiology, 2023)

Bio-fortification of Two Wheat Cultivars with Iron and Zinc Through Their Soil and Foliar Application in Salt-Factored Soil: Growth, Ionic, Physiological, and Biochemical Modifications - Tayyaba Naz; Muhammad Mazhar Iqbal; Shah Fahad; Javaid Akhtar; Muhammad Saqib; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; et al. (Journal of Plant Growth Regulation, 2023)

Green investment, institutional quality, and environmental performance: evidence from G-7 countries using panel NARDL approach - Jiguo Zhao; Saif ur Rahman; Sahar Afshan; Muhammad Sibt E. Ali; Hammad Ashfaq; Sadia Idrees (Environmental Science and Pollution Research, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Phytochemical, biological, and in-silico analysis of Colutea armata Hemsl. & Lace: A possible source of bioactive natural compounds - Ayisha Khalid; Samina Afzal; Farhan Abbas; Iftikhar Afzal; Muhammad Iqbal; Sarfraz Ahmad; Siddique Akber Ansari; Hamad M. Alkahtani; Tahir Ali Chohan; Umair Khurshid; Hammad Saleem; Carlos Leonardo Cespedes-Acuna (South African Journal of Botany, 2023)

Inclusiveness in Food Data Sets: Development of a Food Composition Dataset for South Asian Recipes With Focus on Pakistan - Muhammad Hammad Maqdoom; Syeda Areesha Najam; Shalin Ali; Sana Fatima; Alisha Momin; Abdul Samad; Humaira Jamshed (Journal of Nutrition Education and Behavior, 2023)

Increasing stand stature weakens the positive effects of tree richness and structural imbalance on aboveground biomass in temperate forests: The stand stature hypothesis - Umar Aftab Abbasi; Hammad Gilani; Kiramat Hussain; Arshad Ali (Forest Ecology and Management, 2023)

Insight into the phytochemical, biological, and in silico studies of Erythrina suberosa roxb.: A source of novel therapeutic bioactive products from a medicinal plant - Abdulhakeem S. Alamri; Hammad Saleem; Irfan Pervaiz; Umair Khurshid; Juwairiya Butt; Tahir Ali Chohan; Majid Alhomrani; Marcello Locatelli; Syafiq Asnawi Zainal Abidin; Yasir Nasser H Alqahtani; Kannan R.R. Rengasamy; Mohamad Fawzi Mahomoodally (Food Bioscience, 2023)

A comprehensive review on the botany, traditional uses, phytochemistry, pharmacology and toxicity of Anagallis arvensis (L).: A wild edible medicinal food plant - Hammad Saleem; Umair Khurshid; Muhammad Imran Tousif; Sirajudheen Anwar; Nasser A. Awadh Ali; Mohamad Fawzi Mahomoodally; Nafees Ahemad (Food Bioscience, 2023)

Sedimentary Facies, Architectural Elements, and Depositional Environments of the Maastrichtian Pab Formation in the Rakhi Gorge, Eastern Sulaiman Ranges, Pakistan - Mubashir Mehmood; Abbas Ali Naseem; Maryam Saleem; Junaid ur Rehman; George Kontakiotis; Hammad Tariq Janjuhah; Emad Ullah Khan; Assimina Antonarakou; Ihtisham Khan; Anees ur Rehman; Syed Mamoon Siyar (Journal of Marine Science and Engineering, 2023)
An integrated study of sediments was conducted to examine the facies architecture and depositional environment of the Cretaceous Pab Formation, Rakhi Gorge, and Suleiman Ranges, Pakistan. This research focused on analyzing architectural elements and facies, which are not commonly studied in sedimentary basins in Pakistan. To identify lithofacies, outcrop analysis and section measurement were performed. The identified lithofacies were then categorized based on their depositional characteristics and facies associations, with a total of nine types identified within a stratigraphic thickness of approximately 480 m. These facies were mainly indicative of high-energy environments, although the specifics varied by location. Sedimentary structures such as planar and trough crossbedding, lamination, nodularity, load-casts, and fossil traces were found within these facies, indicating high-energy environments with a few exceptions in calm environments. The identified facies were grouped into seven architectural elements according to their depositional environments: delta-dominated elements, including laminated shale sheet elements (LS), fine sandstone elements (SF), planar cross-bedded sandstone elements (SCp), trace sandstone elements (ST), and paleosol elements (Pa); and river-dominated elements, including trough cross-bedded sandstone elements (SCt), channel deposit elements (CH), and paleosol elements (Pa). These architectural elements, along with their vertical and lateral relationships, indicate a transitional fluvio-deltaic environment within the Pab Formation. In conclusion, by interpreting facies and architectural elements, it is possible to gain a better understanding of the depositional history of the formation and the distribution of reservoir units.

Comparative phytochemical composition, oleuropein quantification, antioxidant and cytotoxic properties of Olea europaea L. leaves - Sirajudheen Anwar; Hammad Saleem; Umair Khurshid; Shabana Yasmeen Ansari; Saleh Alghamdi; Abdul Wali A. Al-Khulaidi; Jonaid Ahmad Malik; Nafees Ahemad; Nasser A. Awadh Ali (Natural Product Research, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Synthesis of novel LaCoO3/graphene catalysts as highly efficient peroxymonosulfate activator for the degradation of organic pollutants - Mohaned Hammad; Steven Angel; Ahmed K. Al-Kamal; Anam Asghar; Amin Said Amin; Mena-Alexander Kräenbring; Haakon T.A. Wiedemann; Vineetha Vinayakumar; Md Yusuf Ali; Paolo Fortugno; Cheolyong Kim; Torsten C. Schmidt; et al. (Chemical Engineering Journal, 2023)

Zeolite amendment reduces lead accumulation and improves growth and yield in tomato plants irrigated with sewage water - Rashid Jawad; Aamir Nawaz; Shaghef Ejaz; Sajid Ali; Muhammad Shahzad Saleem; Hafiz Mohkum Hammad (Environmental Science and Pollution Research, 2023)

Novel modeling and optimization framework for Navy Blue adsorption onto eco-friendly magnetic geopolymer composite - Hammad Khan; Sajjad Hussain; Rehman Zahoor; Muhammad Arshad; Muhammad Umar; Mohsin Ali Marwat; Adnan Khan; Javaid Rabbani Khan; Muhammad Abdul Haleem (Environmental Research, 2023)

Synthesis of waste limestone powder–based alkali-activated binder: experimental, optimization modeling, and eco-efficiency assessment - Mohammed Ibrahim; Mohammed Rizwan Ali; Jobin Jose Iype Joseph; Mohammed Shameem; Mohammed A. Al-Osta; Hammad R. Khalid; Ashraf A. Bahraq (Environmental Science and Pollution Research, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Leaf rolling dynamics for atmospheric moisture harvesting in wheat plant as an adaptation to arid environments - Sabah Merrium; Zulfiqar Ali; Muhammad Hammad Nadeem Tahir; Muhammad Habib-ur-Rahman; Sadia Hakeem (Environmental Science and Pollution Research, 2022)
Plant species surviving in the arid regions have developed novel leaf features to harvest atmospheric water. Before the collected water evaporates, it is absorbed and transported for storage within the tissues and move toward the root zone through the unique chemistry of leaf structures. Deep insights into such features reveal that similarities can be found in the wheat plant. Therefore, this study aimed to evaluate the leaf rolling dynamics among wheat genotypes and their relationships with moisture harvesting and its movement on the leaf surface. For this purpose, genotypes were characterized for leaf rolling at three distinct growth stages (tillering, booting, and spike emergence). The contact angle of leaf surface dynamics (adaxial and abaxial), water budget, and morphophysiological traits of genotypes were measured. The results indicate that leaf rolling varies from inward to twisting type among genotypes and positively affected the water use efficiency and soil moisture difference at all growth stages under normal and drought conditions. Results of wetting property (hydrophilic < 90°) of the leaf surface were positively associated with the atmospheric water collection (4–7 ml). The lower values of contact angle hysteresis (12–19°) also support this mechanism. Thus, genotypes with leaf rolling dynamics (inward rolled and twisted) and surface wettability is an efficient fog harvesting system in wheat for interception and utilization of fog water in drought-prone areas. These results can be exploited to develop self-irrigated and drought-tolerant crops.

Production of Pellets from Furfural Residue and Sawdust Biomass: Effect of Moisture Content, Particle Size and a Binder on Pellet Quality and Energy Consumption - Imran Ahmed; Asif Ali; Babar Ali; Mahdi Hassan; Sakhawat Hussain; Hammad Hashmi; Zafar Ali; Ahsanullah Soomro; Kishan Mukwana (BioEnergy Research, 2022)

Exploring the potential effect of Achnatherum splendens L.–derived biochar treated with phosphoric acid on bioavailability of cadmium and wheat growth in contaminated soil - Muhammad Irfan; Khadim Dawar; Shah Fahad; Imran Mehmood; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2022)

Efficacy of indigenous entomopathogenic fungi for the control of the tomato leafminer Tuta absoluta (Meyrick) in Sudan - Ahmed Mohammed Ali Hammad; Hamas Altibe Abd Alwahed Bashir; Azhari Omer Abdelbagi; Abd Elaziz Sulieman Ahmed Ishag; Mutasim Mohamed Yassin Ali; Magzoub Omer Bashir; Jang-Hyun Hur; Mark Delmege Laing (International Journal of Tropical Insect Science, 2022)

Insecticide residues in Khor Abuhabel sediments and soil of South Kordofan State, Sudan - Amna Osman Mohamed; Azhari Omer Abdelbagi; Abd Elaziz Sulieman Ahmed Ishag; Abdalla Mohammed Abdalla; Ahmed Mohammed Ali Hammad; Jang-Hyun Hur (Arabian Journal of Geosciences, 2022)

Depositional Sedimentary Facies, Stratigraphic Control, Paleoecological Constraints, and Paleogeographic Reconstruction of Late Permian Chhidru Formation (Western Salt Range, Pakistan) - Syed Kamran Ali; Hammad Tariq Janjuhah; Syed Muzyan Shahzad; George Kontakiotis; Muhammad Hussain Saleem; Usman Khan; Stergios D. Zarkogiannis; Panayota Makri; Assimina Antonarakou (Journal of Marine Science and Engineering, 2021)
The Upper Indus Basin, in Pakistan’s western Salt Range, is home to the Zaluch Gorge. The sedimentary rocks found in this Gorge, belonging to the Chhidru Formation, were studied in terms of sedimentology and stratigraphy, and provide new insights into the basin paleogeographic evolution from the Precambrian to the Jurassic period. Facies analysis in the Chhidru Formation deposits allowed the recognition of three lithofacies (the limestone facies—CF1, the limestone with clay interbeds facies—CF2, and the sandy limestone facies—CF3) with five microfacies types (mudstone biomicrite—MF-1, wackestone-biomicrite—MF-2, wackestone-biosparite—MF-3, pack-stone-biomicrite—MF-4, and packstone-biosparite—MF-5), as well as their depositional characteristics. The identified carbonate and siliciclastic formations display various facies in a shallow marine environment, with different lithologies, sedimentary features, and energy conditions. It is thought that the depositional characteristics of these microfacies are closer to those of the middle to outer shelf. Because of the progressively coarsening outcrop sequence, this formation seems to be at the very top of the high stand system tract (HST). A modified dynamic depositional model of the Chhidru Formation is further built using outcrop data, facies information, and stratigraphy. According to this concept, the formation was deposited in the middle to inner shelf area of the shallow marine environment, during the Late-Permian period. The Permo-Triassic Boundary (PTB), which is the end of the type-1 series, is marked by this formation’s top.

Hydrogen Sulfide: A Novel Gaseous Molecule for Plant Adaptation to Stress - Mukhtar Ahmed; Shah Fahad; Muhammad Arif Ali; Sajjad Hussain; Muhammad Tariq; Fariha Ilyas; Shakeel Ahmad; Shah Saud; Hafiz Mohkum Hammad; Wajid Nasim; Chao Wu; Hongyan Liu (Journal of Plant Growth Regulation, 2021)

A new Streptomyces scabies-infecting bacteriophage from Egypt with promising biocontrol traits - Abdelrazek S. Abdelrhim; Abdelmonim Ali Ahmad; Maha O. A. Omar; Adel M. M. Hammad; Qi Huang (Archives of Microbiology, 2021)

Effects of nitrogen fertilization and some non-conventional insecticides on sap sucking pests and yield of transgenic Bt cotton in Sudan - Mamoun Khalafalla Fadlelmawla; Azhari Omer Abdelbagi; Abd Elaziz Sulieman Ahmed Ishag; Ahmed Mohammed Ali Hammad; Jang-Hyun Hur (International Journal of Tropical Insect Science, 2021)

Urtica dioica extracts abolish scopolamine-induced neuropathies in rats - Ali H. Abu Almaaty; Rehab M. Mosaad; Mohamed K. Hassan; Elham H. A. Ali; Ghada A. Mahmoud; Hassan Ahmed; Nahla Anber; Saad Alkahtani; Mohamed M. Abdel-Daim; Lotfi Aleya; Seddik Hammad (Environmental Science and Pollution Research, 2021)

Photocatalytic degradation of crystal violet dye under sunlight by chitosan-encapsulated ternary metal selenide microspheres - Waqar Ahmad; Adnan Khan; Nisar Ali; Sana Khan; Salah Uddin; Sumeet Malik; Nauman Ali; Hamayun Khan; Hammad Khan; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Numerical analysis of special concentric braced frames using experimentally-validated fatigue and fracture model under short and long duration earthquakes - Ali Hammad; Mohamed A. Moustafa (Bulletin of Earthquake Engineering, 2021)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Phytochemical profiling and evaluation of modified resazurin microtiter plate assay of the roots of Trillium govanianum - Kashif Maqbool Khan; Satyajit D. Sarker; Ghazanfar Ali Khan; Hammad Saleem; Shujaat Ali Khan; Abdul Mannan (Natural Product Research, 2020)

Seasonal levels of pesticide residues in the main and the Blue Nile waters in Sudan - Gibreel Abdel latif Ahmed Nesser; Azhari Omer Abdelbagi; Abd Elaziz Sulieman Ahmed Ishag; Ahmed Mohammed Ali Hammad; Mirghani Tagelseed (Arabian Journal of Geosciences, 2020)

Correction to: Nanoceramics and novel functionalized silicate-based magnetic nanocomposites as substitutional disinfectants for water and wastewater purification - Ali B. Abou Hammad; Amany M. El Nahrawy; Bahaa A. Hemdan; Akebe Luther King Abia (Environmental Science and Pollution Research, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Nanoceramics and novel functionalized silicate-based magnetic nanocomposites as substitutional disinfectants for water and wastewater purification - Ali B. Abou Hammad; Amany M. El Nahwary; Bahaa A. Hemdan; Akebe Luther King Abia (Environmental Science and Pollution Research, 2020)

Highlight report: liver to bone communication - Hassan Ahmed; Mohamed S. Ahmed; Alsagher O. Ali; Seddik Hammad (Archives of Toxicology, 2019)

Impacts of Egyptian propolis extract on rat cerebellum intoxicated by aluminum silicate: histopathological studies - Nahed A. Omar; Ali H. Abu-Almaaty; Yasmin M. Abd El-Aziz; Ahmed M. Abdeen; Fatma El Zahraa Ammar Mohamed; Mohamed M. M. Hashem; Seddik Hammad (Environmental Science and Pollution Research, 2019)

Green sol–gel synthesis of novel nanoporous copper aluminosilicate for the eradication of pathogenic microbes in drinking water and wastewater treatment - Bahaa Ahmed Hemdan; Amany Mohamed El Nahrawy; Abdel-Fatah M. Mansour; Ali Belal Abou Hammad (Environmental Science and Pollution Research, 2019)

Ecophysiological response of early stage Albizia lebbeck to cadmium toxicity and biochar addition - Muhammad Talha Bin Yousaf; Muhammad Farrakh Nawaz; Hammad Fayyaz Khawaja; Sadaf Gul; Shafaqat Ali; Irfan Ahmad; Fahd Rasul; Muhammad Rizwan (Arabian Journal of Geosciences, 2019)

A multi-criteria decision analysis of solid waste treatment options in Pakistan: Lahore City—a case in point - Yousaf Ali; Zain Aslam; Hammad Sajid Dar; UbaidUllah Mumtaz (Environment Systems and Decisions, 2018)

Concurrent vaccination of goats with foot and mouth disease (FMD) and peste des petits ruminants (PPR) booster vaccines - Muhammad Khalid Mansoor; Abdullmajeed Hamood Al-Rawahi; Hatim Ali El-Tahir; Badar Al-Faraei; Muhammad Hammad Hussain; Muhammad Nadeem Asi; Ibrahim Al-Hussani; Safwat Sabar (Tropical Animal Health and Production, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Levels of pesticides residues in the White Nile water in the Sudan - Gibreel A. A. Nesser; Azhari O. Abdelbagi; Ahmed Mohammed Ali Hammad; Mirghani Tagelseed; Mark D. Laing (Environmental Monitoring and Assessment, 2016)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Quantification of carbon stock to understand two different forest management regimes in Kayar Khola watershed, Chitwan, Nepal - Purity Rima Mbaabu; Yousif Ali Hussin; Michael Weir; Hammad Gilani (Journal of the Indian Society of Remote Sensing, 2014)

Changes in precipitation extremes over arid to semiarid and subhumid Punjab, Pakistan - Farhat Abbas; Ashfaq Ahmad; Mohammad Safeeq; Shafaqat Ali; Farhan Saleem; Hafiz Mohkum Hammad; Wajid Farhad (Theoretical and Applied Climatology, 2014)

Evaluation of object-based image analysis techniques on very high-resolution satellite image for biomass estimation in a watershed of hilly forest of Nepal - Yousif Ali Hussin; Hammad Gilani; Louise van Leeuwen; M. S. R. Murthy; Rachna Shah; Srijana Baral; Nandin-Erdene Tsendbazar; Saurav Shrestha; Shyam Kumar Shah; Faisal Mueen Qamer (Applied Geomatics, 2014)

Forest cover change assessment in conflict-affected areas of northwest Pakistan: the case of swat and shangla districts - Faisal Mueen Qamer; Sawaid Abbas; Rashid Saleem; Khurram Shehzad; Hassan Ali; Hammad Gilani (Journal of Mountain Science, 2012)